Study Protocol : an exploration of health professional support for breastfeeding - a primary care study - Jahn Kassim, Puteri Shanaz; Awang Dzulkarnain, Dayangku Hayaty; Jamani, Nurjasmine Aida; Abdul Rashid, Aneesa; Shamsuddin, Nurainul Hana; Mawardi, Mawar (2015)
Even though there has been substantial evidence on the benefits of breastfeeding, Malaysia has one of the lowest rates of breastfeeding in Asia. The Malaysia Third National and Health Morbidity Survey (NHMS III) 2006 showed that less than 155 of infants below six months were breastfed exclusively in 2006; and the prevalence of continued breastfeeding up to two years old in Malaysia was 37.4% which is among the lowest compared to the prevalence in other countries in South East Asia. The role of health professionals in promoting and supporting breastfeeding has been increasingly emphasized. However, data on health professional's perspectives on breastfeeding in Malaysia has been lacking. The aim of this study is to understand health professionals' perspectives on breastfeeding, their knowledge and attitudes towards breastfeeding and their self-efficacy in dealing with breastfeeding issues, as well as perceived barriers to providing support and issues around breastfeeding education.